Existence of Brand Loyalty- A Myth or A Reality? - Shetty, Vijetha S. (Indian Journal of Marketing, 2010)
Marketing is nothing but an enigma. It is one of the most dynamic fields in the business arena. Industrial Revolution has given way to that of the Consumer Revolution. Earlier lessons of 4Ps (Product, Price, Place and Promotion) have given way to 4Cs (Consumer, Cost, Convenience and Communication). There has been a fundamental change in consumer’s preference and behaviour. There is now an unprecedented openness to try both-new products and new brands, manifested in a sweeping preference of brand variety and novelty over brand loyalty. The essence of the marketing process is building a brand in the minds of the consumers. In the recent times, it is seen that today’s consumer has the ambition to exhaust as many possibilities as he/she can for the fear to miss out something. It is the Fear of Missing Out (FOMO) phobia. Certainly, this has negative effect on brand loyalty.